2018
DOI: 10.1042/bsr20180820
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-specific 9, a putative secretory protein, induces G2/M arrest and inhibits the proliferation of human embryonic hepatic cells

Abstract: Background: Placenta-specific 9 (Plac9) is a putative secreted protein that was first discovered in the context of embryogenesis. The expression pattern of Plac9 during embryogenesis, together with the results of recent reports, suggest that Plac9 may play a role in the liver development. The present study was conducted to investigate the secretory characteristics of Plac9 and its potential role in liver cell physiology. Methods: Immunofluorescence was employed to identify the subcellular distribution of Plac9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Consistently, MTT and colony formation experiments provided clear evidence that the overexpression of Plac9 could inhibit cell proliferation. The result was consistent with that our previous study showing that Plac9 overexpression inhibits proliferation of human embryo liver cell line, L02 [25]. Furthermore, cell cycle distribution data showed that overexpression of Plac9 in 16HBE could increase S phase population and a corresponding decrease of cells in the G1 phase.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistently, MTT and colony formation experiments provided clear evidence that the overexpression of Plac9 could inhibit cell proliferation. The result was consistent with that our previous study showing that Plac9 overexpression inhibits proliferation of human embryo liver cell line, L02 [25]. Furthermore, cell cycle distribution data showed that overexpression of Plac9 in 16HBE could increase S phase population and a corresponding decrease of cells in the G1 phase.…”
Section: Discussionsupporting
confidence: 93%
“…To explore the role of Plac9 in human bronchial epithelial pathogenesis, we constructed a stable Plac9overexpressing cell line (16HBE-GFP-Plac9) by transfecting the lentiviral Plac9 vector, which expressed both GFP and Plac9 under the control of the constitutive CMV promoter, into the 16HBE cells and a control line (16HBE-GFP) stably expressed only GFP as previously described [25]. Figure 2A showed representative photo of the stable cell lines (16HBE-GFP-Plac9 and 16HBE-GFP).…”
Section: Establishing a Cell Line Stably Expressing Plac9 In Human Brmentioning
confidence: 99%
See 3 more Smart Citations